Legal Studies on Child Adoption in the Indonesian Family Context: A Juridical Review - Lubis, Aldi Subhan; Mina, Revi Fauzi Putra; Nasution, Nabila Fahira (Jurnal Multidisiplin Madani, 2024)
Child adoption is a crucial process in family law, involving the legal acceptance of a non-biologically related child into another family. In Indonesia, adoption safeguards children's rights to a stable family environment, making family law's role pivotal. However, adoption in Indonesia faces challenges like complex procedures, limited information, and bureaucratic delays. This study aims to explore adoption's facets in Indonesia: its legal process, common obstacles, family law's role in safeguarding children's and adoptive parents' rights, and Law Number 23 of 2002's effectiveness in handling adoption cases. Using normative juridical research, this study analyzes secondary data from regulations and literature. Findings reveal the adoption process's intricacies, highlighting issues with legal compliance, children's rights protection, and adoptive parents' responsibilities. Courts play a vital role in ensuring legal certainty for adopted children. Adoption not only involves legal aspects but also emotional challenges for the adopted child. This research enhances understanding of Indonesian adoption and informs better family law policies and practices, aiming to improve adopted children's and adopting families' welfare and protection